«Віртуальний простір» в житті сучасної людини: філософський зріз - Борисова, Тетяна Вікторівна; Кобаченко, Б. В. (Український державний університет науки і технологій, Дніпро, 2025)
UKR: Розглядається широкий горизонт філософських викликів у розумінні ролі віртуальної реальності в житті сучасної людини. Акцентується увага на головних формах впливу штучного інтелекту на особистісні екзистенційні складові – свободу, творчость, пізнання.

ENG: The article considers a wide range of philosophical challenges in understanding the role of virtual reality in the life of a modern person. Attention is focused on the main forms of influence of artificial intelligence on the traditional existential components of the individual - freedom, creativity, cognition.
«Virtual Space» in the Life of a Modern Person: a Philosophical Perspective
Т. Борисова: ORCID 0000-0002-0122-743X
Keywords: людина; віртуальний простір; культура; свобода; штучний інтелект; творчість; human; virtual space; culture; freedom; artificial intelligence; creativity; КМЕіСГД; HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects